Cytological spectrum of lymph node lesions-our institute experience - Dr. Patil Rashmi K.; Dr. Indira Priyadarshini A; Dr. Kittur Shreekant K.; Dr. Haravi Rekha M.; Dr. Aruna S.; Dr. Jadhav Meena N. (Tropical Journal of Pathology and Microbiology, 2017)
Introduction: Lymphadenopathy is of great clinical significance as underlying diseases may range from a treatable infectious etiology to malignant neoplasms. Fine needle aspiration cytology (FNAC) plays a vital role in solving these issues, being recognised as rapid diagnostic technique because of simplicity accuracy and minimal invasion. Aim: To know the cytological spectrum of lymphadenopathy and to understand the burden of disease in this region. Design: This is a retrospective cytological study on 1478 patients including all age groups and both genders presenting with palpable lymphadenopathy over a period of seven years. Materials and Methods: FNAC was conducted with 22-24 gauge needle attached to 20 cc syringes. Smears were stained with Giemsa and Papanicolaou stains routinely; and special stains like Zeihl-Neelsen and periodic acid-Schiff were done whenever required. The data were tabulated as per the involvement of various lymph node groups and type of neoplastic and non-neoplastic lesions involved. Data was analysed using SPSS 22 version. Results: Out of 1478 aspirations of lymph nodes, the most frequent cause of lymphadenopathy was found to be tuberculous lymphadenitis 592 (40.06%) cases. The next frequent diagnosis was reactive lymphadenopathy with 550 (37.2%) cases, followed by metastatic lymphadenopathy in 243 (16.4%) cases. The diagnosis of primary neoplastic lesions was seen in 29 (2.0%) cases. Conclusion: In our study, the predominant cause of lymphadenopathy was tuberculous lymphadenitis, followed by reactive lymphadenopathy and malignant neoplasms especially metastatic carcinoma. FNAC was helpful in diagnosing approximately 98% of cases.